Analysis of the Salivary Microbiome in the Periodontal Disease Patients with Hypertension and Non-hypertension - Li, Suhua; Zaker, Rexidan; Chu, Xueqian; Asihati, Reyida; Li, Chong; Guo, Xin; Jila, Palidan; Sang, Xiaohong (Current Bioinformatics, 2021)
Background: An improved comprehension of the oral microbiota function in the pathogenesis of disease will contribute to the diagnosis and treatment of both hypertension and periodontal disease. In our study, a comparison of the salivary microbiome between hypertension and Non-hypertension cohorts was designed to reveal microbial signatures. Methods: Patients were divided into four sub-groups: Gingivitis, and Periodontitis (stage 2, 3, and 4). Then, hypertension and non-hypertension cohorts were split into periodontal health and periodontitis subgroups. The salivary samples were processed for DNA extraction (n=246). The V3-V4 hypervariable regions of microbiome 16S rRNA genes were amplified. Finally, sequencing libraries were constructed and subjected to bioinformatics and statistical analyses. Results: The oral microbial diversity decreased in both hypertension and periodontal disease groups compared to the healthy ones. At the genus level, the diversity showed 100 different operational taxonomic units (OTUs) for differential abundance testing. The first trend showed OTUs decreased in relative abundance with increasing periodontal disease, as well as hypertension and nonhypertensive groups. For this trend, OTUs comprise of a mix of primarily anaerobic commensals and potential acute diarrhea pathogens. The second trend was that the diversity of genera was decreased in the hypertension group relative to the non-hypertension group, including other anaerobic bacteria related to periodontal disease. Conclusion: Microbiota diversity decreased in the hypertension group and different stages of periodontal disease groups. However, Neisseria and Solobacterium genera increased in the coexisting hypertension and periodontal disease group. Certainly, these findings indicate that the abundance of genera continues to change due to additional stresses caused by co-existing conditions.
Keywords: hypertension